(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
The primary goal of this study was to identify the earnings manipulation of 3 competitive firms (Bharti airtel, Idea, JIO). The recently used model for detecting earnings manipulation is Beneish m-score model. In this study 3 years financial statements are used. (2014-15, 2015-16, 2016-17). The model’s variables are designed to capture either the effects of manipulation or preconditions that may prompt firms to engage in such activity. While the model is implemented the data can be extracted from an annual report of the company.